2016
DOI: 10.1186/s13045-016-0307-9
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-to-mesenchymal plasticity of cancer stem cells: therapeutic targets in hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) remains one of the most common and lethal malignancies worldwide despite the development of various therapeutic strategies. A better understanding of the mechanisms responsible for HCC initiation and progression is essential for the development of more effective therapies. The cancer stem cell (CSC) model has provided new insights into the development and progression of HCC. CSCs are specialized tumor cells that are capable of self-renewal and have long-term repopulation potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
141
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(146 citation statements)
references
References 114 publications
(151 reference statements)
3
141
1
1
Order By: Relevance
“…Elevation in IL-6 expression and loss of E-cadherin have been linked with increase cancer stem cell population in various cancer types [5557]. In this study, we did not observe positivity for cancer stem cells with markers such as CD133, OCT4, or Nanog (data not shown), suggesting that rising or re-populating of cancer stem cells is not the major mechanism by which IL-6 induces prostate tumorigenesis in current model.…”
Section: Discussioncontrasting
confidence: 48%
“…Elevation in IL-6 expression and loss of E-cadherin have been linked with increase cancer stem cell population in various cancer types [5557]. In this study, we did not observe positivity for cancer stem cells with markers such as CD133, OCT4, or Nanog (data not shown), suggesting that rising or re-populating of cancer stem cells is not the major mechanism by which IL-6 induces prostate tumorigenesis in current model.…”
Section: Discussioncontrasting
confidence: 48%
“…2C&D). Since epithelial-to-mesenchymal transition has been recognized as an important regulator of cancer metastasis [17], we investigated whether miR-224 contributes to metastasis in PDAC via the regulation of epithelial-to-mesenchymal transition. We found that miR-224 overexpression promoted the migration of Panc1 cells (Fig.…”
Section: Mir-224 Stimulates Pdac Cancer Cell Proliferation and Migrationmentioning
confidence: 99%
“…Accumulating evidence implicates cancer stem cells (CSCs) in the growth and spread of HCC [61] . CSCs have the capacity for self-renewal and ability to differentiate, and have been identified to confer resistance to chemotherapy.…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…The process of EMT is also a major contributor for metastasis and drug resistance [61] . More recently, exosomes have been described to mediate EMT in many cancers [63] .…”
Section: Epithelial-to-mesenchymal Transitionmentioning
confidence: 99%